Auditorias internas como fonte de informação para o conhecimento organizacional: estudo de caso em uma IFES - Santos, Ludinaura Regina Souza dos (2012)
The main objective of this research was to analyze how the internal audit processes has become themselves as information source for the organizational knowledge in a federal institution of higher education. The theoretical framework was structured into four parts: (1) discussion about organizational knowledge, (2) theory of organizational knowledge creation, (3) public administration control in Brazil, (4) internal governmental audits. Referring to the research characteristics, it presented a multidisciplinary aspect, being descriptive, inductive, and qualitative, adopting the strategy of a case study and using existent documents as research instruments. The context of the case study was the Federal University of Paraiba, once were analyzed the reports of the internal audits, performed by the Internal Control Coordination of this University, taking into account, at least, the audited areas during two consecutive years or not, from 2008 to 2010.For data analysis, it was used Bardin s (2011) content analysis, where report recommendations were identified in audit note, operational faults and indemnity to treasury. Then, these recommendations, which are part of the audit report, were classified and counted, according to their type, in audited area and recommended manager unit, in accordance to their audited area, in order to verify if they were re-incident. The results showed that: the recommendations type operational faults are more incident and re-incident, demonstrating that the activities related to execution and control are more subject to improvement potentials; the incidence and re-incidence levels varies, according to the audited areas and recommended manager unit, existing more recommendations incidence as long as more recommended manager units were audited in the same area; organizational learning has happened from the information, mentioned in the recommendations, which served to correct faults and mistakes, providing the organizational knowledge; finally, the great number of internal audit processes have constituted themselves as information source for the organizational knowledge, once great part of the recommendations consigned in the internal audit report have been implemented until the subsequent audit, ratifying that the information, by the action and attitude, has itself becoming knowledge.